Система управления и настройки в электронном курсе для дистанционного обучения - Лысенков, H. A.; Рогачев, Б. А. (УАДО, 2004)
This article describes the main part of the distance leaming System - configuration environment. This System includes next features: users management, advanced disciplines management, which includes discipline structure, questions, labworks, tasks management. Access level to system bases on current user’s rights, which is resuit of setting determined bits in «access byte»
Keywords: электронный курс обучения; дистанционное обучение